IMPACT OF WEB QUALITY ON EMPLOYEES’ SATISFACTION IN INDONESIA STATE EMPLOYMENT DEPARTMENT - Novanto, Adhitiro; Siregar, Tety Elida; Hidayat, Taufik (Jurnal Ilmiah Informatika Komputer, 2019)
The State Employment Department (BKN) had applied information technology in employee data management since 2011. However, flaws were found in the system, such as occurrence of inaccurate data and complicated navigation. This study was aimed at analyzing the satisfaction of BKN staffs in using DMS web. Web quality was assessed using 3 dimensions: usability, information quality and service information quality. These 3 dimensions were then associated with the satisfaction of BKN staffs as the users. Data was collected through questionnaires to 206 staffs with authorized accesses to the web. The results showed that the quality of three dimensions of the web influenced users’ satisfaction.